Implementasi Teknik Metastasis Berbasis Keluarga dalam Upaya Mewujudkan Kampung Yanggandur Merauke sebagai Kampung Melek Aksara - Henie Poerwandar Asmaningrum; Gerzon Jokomen Maulany; Martha Betaubun; Nasrawati Nasrawati (LPPM Universitas Bumigora, 2021)
The goal of this community service program is to make Yanggandur Village a Literary Literacy Village. The target of this program is 20 families who are still illiterate in Yanggandur Village. The method of implementing the program is a family-based metastasis strategy. Technically, this program is integrated with the Musamus University Community Service Program. 12 students act as the first tutor who will train the executive tutor who is one of the target family members. Furthermore, the executive tutor will teach other family members. At the end of the program, 36% of participants were able to write word for word in one or two sentences fluently and correctly, 56% of participants had been able to read word for word in one or two sentences correctly, and 60% of participants had been able to add and subtract shapes dozens. In conclusion, the implementation of family-based metastasis techniques can improve the ability to write, read, and count in the people of Yanggandur Village Merauke.